Associations of maternal resources with care behaviours differ by resource and behaviour - Basnet, Sulochana; Frongillo, Edward A.; Nguyen, Phuong Hong; Moore, Spencer; Arabi, Mandana (John Wiley & Sons, 2020)
Care is important for children's growth and development, but lack or inadequacy of resources for care can constrain appropriate caregiving. The objectives of this study were to examine whether maternal resources for care are associated with care behaviours specifically infant and young child feeding, hygiene, health‐seeking, and family care behaviours. The study also examined if some resources for care are more important than others. This study used baseline Alive & Thrive household surveys from Bangladesh, Vietnam, and Ethiopia. Measures of resources for care were maternal education, knowledge, height, nourishment, mental well‐being, decision‐making autonomy, employment, support in chores, and perceived instrumental support. Multiple regression analyses were conducted to examine the associations of resources for care with child‐feeding practices (exclusive breastfeeding, minimum meal frequency, dietary and diversity), hygiene practices (improved drinking water source, improved sanitation, and cleanliness), health‐seeking (full immunization), and family care (psychosocial stimulation and availability of adequate caregiver). The models were adjusted for covariates at child, parents, and household levels and accounted for geographic clustering. All measures of resources for care had positive associations with care behaviours; in a few instances, however, the associations between the resources for care and care behaviours were in the negative direction. Improving education, knowledge, nutritional status, mental well‐being, autonomy, and social support among mothers would facilitate provision of optimal care for children.